Nitrogen‐Doped Carbon Nanotube Arrays for High‐Efficiency Electrochemical Reduction of CO2: On the Understanding of Defects, Defect Density, and Selectivity. Issue 46 (25th September 2015) - Sharma, Pranav P.; Wu, Jingjie; Yadav, Ram Manohar; Liu, Mingjie; Wright, Christopher J.; Tiwary, Chandra Sekhar; Yakobson, Boris I.; Lou, Jun; Ajayan, Pulickel M.; Zhou, Xiao‐Dong
Abstract: Nitrogen‐doped carbon nanotubes (NCNTs) have been considered as a promising electrocatalyst for carbon‐dioxide‐reduction reactions, but two fundamental chemistry questions remain obscure: 1) What are the active centers with respect to various defect species and 2) what is the role of defect density on the selectivity of NCNTs? The aim of this work is to address these questions. The catalytic activity of NCNTs depends on the structural nature of nitrogen in CNTs and defect density. Comparing with pristine CNTs, the presence of graphitic and pyridinic nitrogen significantly decreases the overpotential (ca. −0.18 V) and increases the selectivity (ca. 80 %) towards the formation of CO. The experimental results are in congruent with DFT calculations, which show that pyridinic defects retain a lone pair of electrons that are capable of binding CO2 . However, for graphitic‐like nitrogen, electrons are located in the π* antibonding orbital, making them less accessible for CO2 binding. Abstract : Useful defects : The electrochemical activity of nitrogen‐doped multiwalled carbon nanotubes (see picture) used for the reduction of CO2 was improved by tuning the nitrogen defect sites in the wall structure. Pyridinic nitrogen defects supported the selective formation of CO. DFT calculations confirmed the experimental results.